Frontier mosaic voices of Burma from the lands in between - Humphries, Richard (Orchid Press, 2007)
Damning indictment of Burma?s abuse of its citizens and Thailand?s official apathy to the plight of Burmese refugees as recounted by first-hand accounts and the author?s own observations as he traveled the length of the Thai-Burma border